2015
DOI: 10.7314/apjcp.2015.16.6.2177
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of Genetic Mutations in Breast Cancer

Abstract: Breast cancer is the most common malignancy in women around the world. About one in 12 women in the West develop breast cancer at some point in life. It is estimated that 5%-10% of all breast cancer cases in women are linked to hereditary susceptibility due to mutations in autosomal dominant genes. The two key players associated with high breast cancer risk are mutations in BRCA 1 and BRCA 2. Another highly important mutation can occur in TP53 resulting in a triple negative breast cancer. However, the great ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 112 publications
2
52
0
5
Order By: Relevance
“…Here, we reported that the tracking of MYC expression in CTCs was feasible and it might be of interest in BC patients, in agreement with Reinhardt and colleagues, who described high MYC expression in CTCs' differential phenotypes in BC [49]. Regarding PALB2 (Partner And Localizer of Breast Cancer Type 2 susceptibility protein (BRCA2)), mutations in this gene have been associated with increased risk of BC [50]. PALB2 acts as a tumor suppressor protein by mediating DNA repair and thereby suppressing genome instability [51].…”
Section: Discussionsupporting
confidence: 87%
“…Here, we reported that the tracking of MYC expression in CTCs was feasible and it might be of interest in BC patients, in agreement with Reinhardt and colleagues, who described high MYC expression in CTCs' differential phenotypes in BC [49]. Regarding PALB2 (Partner And Localizer of Breast Cancer Type 2 susceptibility protein (BRCA2)), mutations in this gene have been associated with increased risk of BC [50]. PALB2 acts as a tumor suppressor protein by mediating DNA repair and thereby suppressing genome instability [51].…”
Section: Discussionsupporting
confidence: 87%
“…2) bedeutend. Im Vergleich zu sporadisch auftretenden Malignomen werden diese in signifikant jüngerem Alter manifest [18]. Frauen mit schwangerschaftsassoziiertem Mammakarzinom tragen insgesamt betrachtet häufiger ebendiese genetischen Prädispositionen in sich als nicht schwangere Frauen aus Vergleichspopulationen [19].…”
Section: Genetikunclassified
“…Early menarche and late menopause ensure a longer exposure to the hormone estrogen thus increasing the risk of BC (7). Various studies have identi ed the variations in high penetrant genes like BRCA1, BRCA2, PTEN, TP53, CDH1, and STK11 along with moderate penetrant genes such as CHEK2, BRIP1, ATM and PALB2 (8,9) and their association with BC. There are about 182 loci that have been identi ed and are susceptible to BC (10) which accounts for 30% of the genetic heritability of BC (11).…”
Section: Introductionmentioning
confidence: 99%